Methods for Enhancing Clustered Regularly Interspaced Short Palindromic Repeats/Cas9-Mediated Homology-Directed Repair Efficiency - Tang, Xi-Dian; Gao, Fei; Liu, Ming-Jie; Fan, Qin-Lei; Chen, De-Kun; Ma, Wen-Tao (Frontiers in Genetics, 2019)
The evolution of organisms has provided a variety of mechanisms to maintain the integrity of its genome, but as damage occurs, DNA damage repair pathways are necessary to resolve errors. Among them, the DNA double-strand break repair pathway is highly conserved in eukaryotes, including mammals. Non-homologous DNA end joining and homologous directed repair are two major DNA repair pathways that are synergistic or antagonistic. Clustered regularly interspaced short palindromic repeats genome editing techniques based on the non-homologous DNA end joining repair pathway have been used to generate highly efficient insertions or deletions of variable-sized genes, but are error-prone and inaccurate. By combining the homology-directed repair pathway with clustered regularly interspaced short palindromic repeats cleavage, more precise genome editing via insertion or deletion of the desired fragment can be performed. However, homologous directed repair is not efficient and needs further improvement. Here, we describe several ways to improve the efficiency of homologous directed repair by regulating the cell cycle, expressing key proteins involved in homologous recombination, and selecting appropriate donor DNA.